craftBlend - Masa Lubbadeh; Raya Hindi (My University, 2025)
In the last few years, we noticed that people tend to open their own businesses and started promoting their work on social media. At the beginning, it was very effective, convenient and their content reached the targeted audience. This tempted many people to start their own businesses, which has led to an increase in the number of small business accounts on social media, resulting in businesses facing increasing pressure to have a widespread online presence. Our project’s objective is to develop a user-friendly platform for small businesses, giving them their own space to display and sell their work. By providing a platform customized to their needs, we aim to help these businesses grow and reach a wider audience. The platform will also organize the process of handling customer orders, ensuring efficiency and convenience for both the business owner and the customer. We offer many features in our project, customers will be able browse through different categories, when they select their preferred category, the platform will display all the small business accounts available under that category. Customers can then explore the work of each business, view products, check details, and place orders directly. Additionally, customers will have the option to place special or custom orders, allowing them to request personalized products according to their preferences. Moreover, customers will have the option to interact with the business owners, ask questions, and leave feedback or reviews. There are many applications today that focus on specific industries or individual businesses, but our project is designed to serve a broader range of small enterprises. Many of these businesses would need to create their own applications to meet their unique needs, which can be both time-consuming and costly. Our project simplifies this process by offering a flexible platform that allows small businesses to easily join our system, providing them with the tools they need to increase their visibility and manage orders efficiently.